2004
DOI: 10.1002/ar.a.20081
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system regulation of liver repair

Abstract: This chapter reviews recent evidence that the sympathetic nervous system (SNS) regulates liver repair by modulating the phenotypes of hepatic stellate cells (HSCs), the liver's principal fibrogenic cells, and hepatic epithelial progenitors, i.e., oval cells. SNS nerve fibers touch HSCs and these cells express adrenoceptors, suggesting that HSCs may be targets for SNS neurotransmitters. HSCs also contain catecholamine biosynthetic enzymes, release norepinephrine (NE), and are growth-inhibited by adrenoceptor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 56 publications
2
64
0
1
Order By: Relevance
“…We propose an inhibition of the fibrogenic properties in fibroblasts involved in sclerosing cholangitis because fibroblasts of different tissues were shown to express the whole subset of b-adrenoceptors. 33,34 Therefore, fibroblasts may be directly affected by the inhibition of b-adrenoceptors in a manner similar to that recently described for HSC by Oben et al 10 As vagotomy has been shown to reduce bile flow, whereas elevated levels of neuropeptide Y increase the bile flow, improvement after b-adrenoceptor inhibition could also be a matter of altered bile composition or reduced bile flow. 35 In addition, an indirect effect on fibrosis is also suggested because the RAS is highly controlled by the SNS.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…We propose an inhibition of the fibrogenic properties in fibroblasts involved in sclerosing cholangitis because fibroblasts of different tissues were shown to express the whole subset of b-adrenoceptors. 33,34 Therefore, fibroblasts may be directly affected by the inhibition of b-adrenoceptors in a manner similar to that recently described for HSC by Oben et al 10 As vagotomy has been shown to reduce bile flow, whereas elevated levels of neuropeptide Y increase the bile flow, improvement after b-adrenoceptor inhibition could also be a matter of altered bile composition or reduced bile flow. 35 In addition, an indirect effect on fibrosis is also suggested because the RAS is highly controlled by the SNS.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, HSCs are able to biosynthesize catecholamines because of their subset of metabolizing enzymes. 10 The inhibition of fibrogenic features of HSCs by blockade of the adrenoceptors was supported by studies of Dubuisson et al These authors demonstrated that sympathectomy after 6-hydroxydopamine application leads to 60% reduction of fibrosis after CCL4 intoxication. 25 Our studies using the Mdr2 À/À model now proves that the blockade of b-adrenoceptors by propranolol results in a significant deceleration of fibrosis progression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…5 However, these cells also exhibit many neuroendocrine features, including the expression of synaptophysin, glial fibrillary acidic protein (GFAP), neural cell adhesion molecule, nestin, 6 neurotrophins, 7 dopamine-b-hydroxylase (DBH), and tyrosine hydroxylase. 8 Like neuroendocrine cells, HSC synthesize a variety of catecholamines and express adrenoreceptors, 9 as well as receptors for other neurohumoral factors, such as acetylcholine, 10 neuropeptide Y, 11 angiotensin, 12 somatostatin, 13 and leptin. 14 These features have prompted speculation that HSC might be derived from neural precursors during development.…”
mentioning
confidence: 99%
“…It is interesting that the sympathetic nervous system has been implicated in the regulation of liver repair (see [191]). Since ATP is now well established as a cotransmitter with NA in sympathetic nerves, it may be a source of ATP involved in liver regeneration.…”
Section: Regeneration Of Livermentioning
confidence: 99%